2018
DOI: 10.1002/pmic.201700290
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and iTRAQ‐Based Quantitative Proteomics Analysis of Methyl Jasmonate–Induced Tolerance in Brassica napus Under Arsenic Stress

Abstract: Brassica napus plants exposed to 200 μM arsenic (As) exhibited high-level of stress condition, which led to inhibited growth, enhanced lipid peroxidation, and disrupted cellular ultrastructures. Exogenous application of methyl jasmonate (MeJA) alleviated the As-induced oxidative stress and improved the plant growth and photosynthesis. In this study, changes in the B. napus leaf proteome are investigated in order to identify molecular mechanisms involved in MeJA-induced As tolerance. The study identifies 177 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Ahmad et al (2017) have also suggested that JA mitigates the deleterious effects of Cd stress in Vicia faba by preventing the accumulation of Cd, H 2 O 2 , and MDA and by increasing proline, glycine betaine, SOD, CAT, APX, and GR activities which reduced the oxidative stress. Recently, Farooq et al (2018) have also reported that exogenous application of MJ to Brassica napus plants alleviated the arsenic-induced oxidative stress and improved overall plant growth and photosynthesis.…”
Section: Role Of Ja Under Heavy Metal/metalloid Induce Toxicitymentioning
confidence: 97%
“…Ahmad et al (2017) have also suggested that JA mitigates the deleterious effects of Cd stress in Vicia faba by preventing the accumulation of Cd, H 2 O 2 , and MDA and by increasing proline, glycine betaine, SOD, CAT, APX, and GR activities which reduced the oxidative stress. Recently, Farooq et al (2018) have also reported that exogenous application of MJ to Brassica napus plants alleviated the arsenic-induced oxidative stress and improved overall plant growth and photosynthesis.…”
Section: Role Of Ja Under Heavy Metal/metalloid Induce Toxicitymentioning
confidence: 97%
“…It can be seen that sequence coverages of the identified proteins were mostly below 30%, and most of the identified proteins were in the mass range 20-30 KD and 30-40 KD (Figure 1b,c). metabolism, and secondary metabolites [44]. Alvarez et al investigated the changes in protein redox regulation in response to oxidative stress induced by MeJA in Arabidopsis shoots and roots using quantitative proteomics approach and confirmed cysteine residues of proteins were involved in redox regulation, which provided a deeper understanding of the jasmonate signaling and regulation network [45].…”
Section: Overview Of Protein Identified In Ws and Opr3-1mentioning
confidence: 99%
“…Guo et al used an iTRAQ-based quantitative proteomics approach to analyze broccoli sprouts treated with exogenous jasmonic acid and found that photosynthesis and protein synthesis were inhibited after JA treatment, which was responsible for the slower growth of broccoli, but carbon metabolism and amino acid metabolism-related proteins were up-regulated [43]. Farooq et al investigated MeJA-induced Arsenic tolerance in Brassica napus leaves using iTRAQ and 110 differentially regulated proteins were identified-proteins that were involved in stress and defense, photosynthesis, carbohydrates and energy production, protein metabolism, and secondary metabolites [44]. Alvarez et al investigated the changes in protein redox regulation in response to oxidative stress induced by MeJA in Arabidopsis shoots and roots using quantitative proteomics approach and confirmed cysteine residues of proteins were involved in redox regulation, which provided a deeper understanding of the jasmonate signaling and regulation network [45].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only cysteine-containing peptides are analyzed, impairing the quantification of those that do not contain this aminoacid. Many more studies to quantify plant proteins have adopted isobaric tags for relative and absolute quantitation (iTRAQ) [ 108 , 109 , 110 ] and tandem mass tags (TMT) [ 111 ]. In comparison to ICAT, or ICPL [ 112 ], TMT and iTRAQ labeling takes place at the peptide level by means of amine specific reagents which assure a wider peptide labeling without loss of PTM information.…”
Section: Omic Technologies In the Plant World: From Genomics To Mementioning
confidence: 99%